Fair Opportunity in Education: A Democratic Equality Perspective. - Anderson, Elizabeth (Ethics, 2007)
The article discusses equal opportunity in education and the responsibilities that the educated have toward society. The author states that academic debated on equality in education has shifted from a standard of equality to adequacy, so that children from rich and poor areas attain an adequate level of academic achievement. The author contends that we must reframe that debate from a focus on the individual to what responsibilities educated people have toward society.